MOTIVASI PEREMPUAN BERWIRAUSAHA MELALUI KELOMPOK ARISAN PROGRAM PEMBERDAYAAN MASYARAKAT (PKK) DI KOTA PEKANBARU - novita novita (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: Being a motivational issue of women in building a creative economy, includingwhen associated with family affairs. Using descriptive method using a sample housewife whojoined in the gathering, then distributed questionnaires regarding the motivation of women tobuild a creative economy. The results obtained with regard to the motivation of womenbuilding a creative economy, as follows: eight domensi motivation of women, among others:driven by the necessities of life, and a sense of fun social activities, happy to get together,socialize, earning himself and of his own business, independent and able show independencecan be known to the highest dimension is the dimension of pleasure gathered, hoping to earntheir own income, can be self-sufficient with a score of 4.5, which means high motivation.Whereas the lowest was in happy groups to socialize, this is because the problem of husband'spermission to gather together the mothers that sometimes social gathering for their householdaffairs unfinished, time to gather more limited. Then because of the benefits also gathered thathave been rated yet maximal.Provedthat savings and loans groups have a significant influence(p.0.006> 0.05) on the motivation of female entrepreneurship.Keywords: Entrepreneurship motivation women, arisan groups.